Effective communication and patient safety among nurses in perioperative settings: a best practice implementation project. (11th September 2022) - Nedelcu, Catalin Marian; Niculiă, Oana Otilia; Nedelcu, Viorica; Zazu, Mariana; Mazilu, Doina Carmen; Klugarová, Jitka; Klugar, Miloslav
ABSTRACT: Objectives: The aim of this implementation project was to promote evidence-based best practice regarding effective communication and patient safety amongst nurses in perioperative settings. Introduction: One of the main causes of surgical errors is inadequate communication. To address this issue, published research has shown that effective communication among healthcare professionals (HCPs) within and between all phases of perioperative care, as well as the proper transfer of all patient information at all transition points, are essential for ensuring patient safety and quality of care. Methods: This best practice implementation project was conducted based on the JBI implementation model and included three phases of activity: a baseline audit, a strategies implementation stage and a follow-up audit. The audit criteria used were based on a JBI evidence summary and referred to: education, interdisciplinary team, conflict resolution, team communication, transfer of patient information and safety intraoperative processes. The project was carried out in the perioperative environment of a university hospital, and the sample included 52 nurses. Results: Eleven audit criteria were used in the baseline audit. For four of these criteria (on education and information transfer) the compliance was zero, for five criteria (on intraoperative processes) the compliance had values between 31 and 66% and for two criteria (on interdisciplinary team/conflict resolution documentation and team communication monitoring), the identified compliance was maximum (100%). Following the identification of four barriers to compliance and the implementation of targeted strategies, the follow-up audit showed complete compliance (100%) for all criteria except three, for which the identified compliance values were 96, 95 and 25%. Conclusion: The implementation of appropriate strategies in this project has led to a significant improvement in nurses' compliance with all audit criteria except one, regarding the verbal transfer of patient information. However, future audits and strategies are needed not only to support the improvements obtained but also to significantly increase the compliance rate for the audit criterion for which only a slight increase in compliance was recorded.